Role of stress and early-life stress in the pathogeny of inflammatory bowel disease - Bonaz, Bruno; Sinniger, Valérie; Pellissier, Sonia (Frontiers in Neuroscience, 2024)
Numerous preclinical and clinical studies have shown that stress is one of the main environmental factor playing a significant role in the pathogeny and life-course of bowel diseases. However, stressful events that occur early in life, even during the fetal life, leave different traces within the central nervous system, in area involved in stress response and autonomic network but also in emotion, cognition and memory regulation. Early-life stress can disrupt the prefrontal-amygdala circuit thus favoring an imbalance of the autonomic nervous system and the hypothalamic-pituitary adrenal axis, resulting in anxiety-like behaviors. The down regulation of vagus nerve and cholinergic anti-inflammatory pathway favors pro-inflammatory conditions. Recent data suggest that emotional abuse at early life are aggravating risk factors in inflammatory bowel disease. This review aims to unravel the mechanisms that explain the consequences of early life events and stress in the pathophysiology of inflammatory bowel disease and their mental co-morbidities. A review of therapeutic potential will also be covered.